ANALISIS RAMADHAN EFFECT PADA PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novanjani Eka Aisyah (2021)
This research is a quantitative study which aims to determine the difference between Abnormal Return and Trading Volume Activity before and after Ramadan. In addition, this study aims to determine the effect before and after Ramadan on Abnormal Return and Trading Volume Activity. This study uses the Food and Beverages sub-sector companies that are listed continuously on the Indonesia Stock Exchange (BEI), namely 20 companies as samples. Hypothesis testing in this study used paired sample t test with SPSS version 23 and t test with Eviews 11. The results of the test showed that there was a significant difference in Abnormal Return before and after Ramadan, but there was no significant difference in Trading Volume Activity before and after Ramadan. In addition, there is an influence after Ramadan on Abnormal Return, but there is no influence before Ramadan on Abnormal Return and Trading Volume Activity, and there is no influence after Ramadan on Trading Volume Activity.